BenchStab: a tool for automated querying of web-based stability predictors - Velecký, Jan; Berezný, Matej; Musil, Milos; Damborsky, Jiri; Bednar, David; Mazurenko, Stanislav (Bioinformatics (Oxford, England), 2024)
SUMMARY: Protein design requires information about how mutations affect protein stability. Many web-based predictors are available for this purpose, yet comparing them or using them en masse is difficult. Here, we present BenchStab, a console tool/Python package for easy and quick execution of 19 predictors and result collection on a list of mutants. Moreover, the tool is easily extensible with additional predictors. We created an independent dataset derived from the FireProtDB and evaluated 24 different prediction methods. AVAILABILITY AND IMPLEMENTATION: BenchStab is an open-source Python package available at https://github.com/loschmidt/BenchStab with a detailed README and example usage at https://loschmidt.chemi.muni.cz/benchstab. The BenchStab dataset is available on Zenodo: https://zenodo.org/records/10637728.
Keywords: Software; Proteins; software; Computational Biology; internet; databáze proteinů; Internet; proteiny; Databases, Protein; Protein Stability; stabilita proteinů; výpočetní biologie